Assessment of aortic valve area on cardiac computed tomography in symptomatic bicuspid aortic stenosis: Utility and differences from Doppler echocardiography - Kim, Kyu; Lee, Soo Ji; Seo, Jiwon; Suh, Young Joo; Cho, Iksung; Hong, Geu-Ru; Ha, Jong-Won; Kim, Young Jin; Shim, Chi Young (Frontiers in Cardiovascular Medicine, 2022)
Backgrounds: This study aimed to investigate the usefulness of geometric orifice area (GOA) on cardiac computed tomography (CT) and differences with effective orifice area (EOA) on Doppler echocardiography in patients with bicuspid aortic stenosis (AS). Methods: One-hundred sixty-three patients (age 64 ± 10 years, 56.4% men) with symptomatic bicuspid AS who were referred for surgery and underwent both cardiac CT and echocardiography within 3 months were studied. For the aortic valve area, GOACT was measured by multiplanar CT planimetry, and EOAEcho was calculated by continuity equation with Doppler echocardiography. The associations of GOACT and EOAEcho with the patients’ symptom scale, biomarkers, and left ventricular (LV) functional variables were analyzed. Results: There was a significant but modest correlation between EOAEcho and GOACT (r=0.604, p<0.001). Both EOAEcho and GOACT revealed significant correlations with mean pressure gradient and peak transaortic velocity and the coefficients were higher in EOAEcho than GOACT. EOAEcho of 1.05 cm2 and GOACT of 1.25 cm2 correspond to the hemodynamic cut-off values for diagnosing severe AS. EOAEcho was well correlated with patients’ symptom scale and log NT-pro BNP, but GOACT was not. In addition, EOAEcho showed higher correlation coefficient with estimated LV filling pressure and LV global longitudinal strain than GOACT. Conclusions: GOACT can be used to evaluate the severity of bicuspid AS. The threshold for GOACT for diagnosing severe AS should be applied higher than that for EOAEcho. However, EOAEcho is still the method of choice because EOAEcho showed better correlation with clinical and functional variables than GOACT.